Hyperglycemia and its Association with Patients’ Mortality Among the Patients Presenting with Acute Stroke in Tertiary Care Hospital - Rana, Maryam; khattak, Abdul Latif; Khan, Muhammad Khalid Azam; Khan, Raees Iqbal; Shah Bukhari, Syed Karamat Hussain; Mehmood, Faisal (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To estimate the occurrence of hyperglycemia in patients with cerebrovascular accident (ischemic) to compare the frequency of mortality among the patients with and without hyperglycemia presenting with acute CVA.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Department of General Medicine, Combined Military Hospital Quetta Pakistan, from May 2018 to May 2019Methodology: A total of 347 patients of both genders diagnosed with acute stroke were included. Blood glucose levels were evaluated and hyperglycemic and normo-glycemic patients were identified. CT scan was performed. Standard treatment was provided to the patients according to the type of stroke (ischemic or hemorrhagic). These patients were discharged.Results: Patients in this study was having age range of 20 to 70 years.SO mean age of 53.76 ± 9.08 years. Many patients 283 (81.56%) were of 45-71 years of age. 183 (52.74%) were of male gender and 164 (47.26%) were females. We have found hyperglycemia in 96 (27.67%) patients. There was no hyperglycemia observed in 251(72.33%) patients. Frequency of hyperglycemia was 12.97%. Frequency of mortality was 30.21% in hyperglycemic patients vs. 6.37% in normo-glycemic patients (p=0.0001).Conclusion: Frequency of hyperglycemia with acute stroke is high with high mortality among the patients presenting with acute stroke as compared to normo-glycemic.